Refining OVCAR ‐3 xenograft models of peritoneal carcinomatosis in nu/nu mice: Comparative intraperitoneal implantation strategies and the role of basement membrane matrix - M. Teresa Perelló‐Trias; Antonio Jose Serrano‐Muñoz; Juan J. Segura‐Sampedro; Adriana M. Quintero‐Duarte; Joana M. Ramis; Marta Monjo (Animal Models and Experimental Medicine, 2026)
Abstract Background Ovarian cancer (OC) is often diagnosed at advanced stages, with extensive peritoneal carcinomatosis (PC) and poor prognosis. Although intraperitoneal drug delivery systems (iDDS) are promising for targeting residual microscopic disease after cytoreductive surgery, reproducible murine PC models remain limited. We compared two OVCAR‐3‐based intraperitoneal engraftment strategies (diffuse vs. localized) and assessed the impact of inoculum density and basement membrane extract (BME) supplementation to identify a robust model for iDDS evaluation. Methods Immunodeficient female nu/nu mice were engrafted with luciferase‐expressing OVCAR‐3 cells. For localized implantation, 1 × 10 6 or 4 × 10 6 cells were implanted into the preperitoneal space behind the rectus abdominis; after assessment, the 1 × 10 6 group was tested with basement membrane extract (BME). In the intraperitoneal dissemination model, 1 × 10 6 cells were injected with BME to promote diffuse peritoneal spread. Tumor progression was monitored weekly using bioluminescence imaging (BLI), and animals were sacrificed for macroscopic, histological, and immunohistochemical analyses. Results In the localized model, no differences were detected between 1 × 10 6 and 4 × 10 6 cells; therefore, 1 × 10 6 was selected for subsequent experiments. BME increased early tumor volume and attenuated the initial BLI decline, but signal and tomographic measurements progressively decreased. Histology revealed extracellular matrix remodeling, apoptosis, and tumor regression, indicating limited long‐term viability. In contrast, the intraperitoneal injection model generated a clinically relevant dissemination pattern. After an initial decrease, BLI increased steadily, and necropsy confirmed tumor nodules along abdominal organ surfaces. Conclusions The intraperitoneal injection model with BME more accurately reproduced human PC progression and distribution, providing a platform for preclinical testing of localized iDDS.